دور الذكاء اللغوي في قراءة النصوص العربية غير المشكّلة: دراسة وصفية لدى طلاب قسم تعليم اللغة العربية بجامعة الإسلامية الحكومية رادين إينتان لامبونج - Najwa Sabillah Estimas; Ahmad Nur Mizan; Damanhuri; Ahmad Basyori (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2026)
This study aims to describe the role of linguistic intelligence in reading non-vocal (unvoweled) Arabic texts among students of the Arabic Language Education program at UIN Raden Intan Lampung. Using a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and documentation involving five purposively selected students who had completed the Arabic reading course. The results show that linguistic intelligence contributes to reading through three interrelated mechanisms: analyzing morphological patterns (sharf) to infer case endings (i’rab) without diacritical marks, using grammatical and semantic context to resolve ambiguity in homographic word forms, and linking a word’s syntactic function to the overall meaning of the sentence before finalizing the reading. Students with higher linguistic intelligence apply these analytical processes automatically and read fluently and confidently, whereas students with limited linguistic competence rely on literal, word-by-word reading and struggle at points requiring case-ending judgments and the interpretation of complex sentences. The specific contribution of this study lies in showing that linguistic intelligence does not translate into reading skill automatically, but operates through a graded cognitive pathway from morphological analysis to contextual interpretation to meaning construction. Theoretically, this deepens understanding of how linguistic intelligence operates within the theory of multiple intelligences; practically, it informs the design of reading-instruction strategies that specifically train this analytical pathway.